2017
DOI: 10.26633/rpsp.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya: important lessons from the Jamaican experience

Abstract: Objectives. To describe the clinical presentation of chikungunya virus (CHIKV) illness in adults during the 2014 outbreak in Jamaica and to determine the predictive value of the case definition. Methods. A cross-sectional study was conducted using clinical data from suspected cases of CHIKV that were reported to the Ministry of Health in April – December 2014. In addition, charts were reviewed of all individuals over 15 years of age with suspected CHIKV based on a diagnosis of CHIKV or “acute viral illness” th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported on Reunion Island and during other investigations. 12,14,20,[36][37][38]43,[47][48][49][50] These trends could be explained by the fact that a higher humoral immune response during acute CHIK infection phase could be associated with evolution toward chronic stage CHIK and persistent arthlagia. 51 Indeed, women, as compared with men, are known to have a stronger humoral immune system linked to female hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics and consequences of CHIKV infection in Caribbean populations have been described (5,(12)(13)(14). However, only two English-speaking Caribbean countries [US Virgin Islands (USVI) and Jamaica] have published reports of the infection (15)(16)(17). Duncan et al highlighted the clinical presentation of CHIKV illness during the acute phase of the disease in Jamaica (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, only two English-speaking Caribbean countries [US Virgin Islands (USVI) and Jamaica] have published reports of the infection (15)(16)(17). Duncan et al highlighted the clinical presentation of CHIKV illness during the acute phase of the disease in Jamaica (17). An investigation by Feldstein et al of the long-term outcomes of the disease in the USVI showed a 2.5-and 2.9-fold increased risk for persistent arthralgia at 6 and 12 months, respectively, after the acute phase (16).…”
Section: Introductionmentioning
confidence: 99%